The Effectiveness of Social Restriction Policies in Handling COVID-19: A Comparative Study of Timor-Leste and Indonesia - Tibersio Barreto (Yayasan Tranformasi Aksara Digital, 2024)
The COVID-19 pandemic has become a global challenge that forces every country to implement adaptive and responsive legal policies in an effort to mitigate its spread. This research aims to compare the COVID-19 handling policies in Timor-Leste and Indonesia in the perspective of responsive law. The method used is normative juridical research with a statutory and conceptual approach, which examines the regulations and legal policies of the two countries in handling the pandemic. The results showed that Timor-Leste was quicker to take steps by closing access to the country through the Estadu de Emergencia mechanism as the main prevention strategy, while Indonesia implemented Large-Scale Social Restrictions (PSBB) and the Enforcement of Restrictions on Community Activities (PPKM) which were more flexible and adjusted the epidemiological conditions in each region. From a responsive law perspective, both countries show efforts in adjusting policies to protect the public, although there are differences in the formulation of regulations, the level of health infrastructure readiness, and the effectiveness of policy implementation. In conclusion, the successful implementation of responsive law in handling a pandemic is highly dependent on the flexibility of regulations and the readiness of the state to respond to changes in emergency conditions quickly and effectively.